UPAYA UKRAINA MENGHADAPI RUSIA ATAS ANEKSASI SEMENANJUNG CRIMEA TAHUN 2014 - Mega Chintia Gunadi; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aimed to describe the efforts of Ukraine after the annexation Crimea on Rusia. The problem appear since Ukraine President Viktor Yakunovych cancelled the associ-ation agreement with European Union (UE) that made citizens demonstrated to make Ya-kunovych descend. The new government had been rejected by Ukraine citizens and demon-strated to rejected the new government (pro UE).The perspective that applied in this reserch is realist, state level analysis, and also use theory security strategy. This theory talks about to securitization of their own state.Threats appear because the different perception or interest between interactions from two sides.Russia as super power state (economy and military) unbalance with Ukraine. There-fore, strategy Ukraine to protect their state by changing their foreign policy into Pro West (United States of America, European Union and North Atlantic Treaty Organization) to give sanctions for Russia, to protect Ukraine from influence of Russia, and to get acknowledge-ment that the referendum of Crimea was not validKeywords: Ukraine ,Russia, Annexation, Respons, Crimea, European Union, NATO